Fecundity and Gonado-somatic Index of Sardinella gibbosa (Bleeker, 1847) of Kanyakumari, South-East Coast of India - Bai, S. Mary Mettilda; Antilda, J.; Mary, Vinoliya Josephine; S.Lazarus (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Fecundity and gonado-somatic index of Sardinella gibbosa was estimated during January to December, 2019. Fecundity ranged from 4941 to 23465 with an average of 10343 eggs per fish. The correlation coefficient of fecundity and body parameters were found to be moderate with TL(r = 0.755), positively correlated with BW and GW (r = 0.900 and r = 0.966). In the case of male maturity size ranged between 12.8 cm and 16.3cm, with an average of 14.5 cm, but in the case of female it was between 12.7cm and 16.5 cm with an average of 14.6cm. Females dominated the commercial catches of the study area, with an annual male-female ratio 1:1.4 and it was significantly different. The spawning season was between April and August with peak during July.